Number of chamber measurement locations for accurate quantification of landscape-scale greenhouse gas fluxes: Importance of land use, seasonality, and greenhouse gas type - Wangari, E.G.; Mwanake, R.M.; Kraus, D.; Werner, C.; Gettel, G.M.; Kiese, Ralf; Breuer, L.; Butterbach-Bahl, Klaus; Houska, T. (American Geophysical Union, 2022)
Accurate quantification of landscape soil greenhouse gas (GHG) exchange from chamber measurements is challenging due to the high spatial-temporal variability of fluxes, which results in large uncertainties in upscaled regional and global flux estimates. We quantified landscape-scale (6 km2 in central Germany) soil/ecosystem respiration (SR/ER-CO2), methane (CH4), and nitrous oxide (N2O) fluxes at stratified sites with contrasting landscape characteristics using the fast-box chamber technique. We assessed the influence of land use (forest, arable, and grassland), seasonality (spring, summer, and autumn), soil types, and slope on the fluxes. We also evaluated the number of chamber measurement locations required to estimate landscape fluxes within globally significant uncertainty thresholds. The GHG fluxes were strongly influenced by seasonality and land use rather than soil type and slope. The number of chamber measurement locations required for robust landscape-scale flux estimates depended on the magnitude of fluxes, which varied with season, land use, and GHG type. Significant N2O-N flux uncertainties greater than the global mean flux (0.67 kg ha−1 yr−1) occurred if landscape measurements were done at <4 and <22 chamber locations (per km2) in forest and arable ecosystems, respectively, in summer. For CO2 and CH4 fluxes, uncertainties greater than the global median CO2-C flux (7,500 kg ha−1 yr−1) and the global mean forest CH4-C uptake rate (2.81 kg ha−1 yr−1) occurred at <2 forest and <6 arable chamber locations. This finding suggests that more chamber measurement locations are required to assess landscape-scale N2O fluxes than CO2 and CH4, based on these GHG-specific uncertainty thresholds.